GOLF CLUB HOUSE DI SPORT CENTER BANJARBARU - Mia Audina; Mohammad Ibnu Saud (JURNAL TUGAS AKHIR MAHASISWA LANTING, 2021)
The planning of the golf venue at the Banjarbaru Sport Center by the government that prioritizes golfers in the field of achievement must of course have complete facilities and national standards in order to accommodate when South Kalimantan hosts a golf tournament at the national level, the main facility in a golf venue is the Golf Club House which acting as a place of preparation for golfers before or after playing in the field, this club house must not only accommodate the golf course it serves in order to create a bond between the club house and the golf course and provide a sense of comfort for its visitors. To solve these problems, the functional Architecture method and the User Experience concept are used which pay attention to four points in the design, namely air exchange, lighting, materials and exposure to solar heat